THE SIGNIFICANCE OF NATIONAL CULTURAL ELEMENTS IN ENGLISH AND UZBEK FOLK SONGS - Yusupova Gulizebo Yangibayevna (Western European Studies, 2024)
Folk songs play a vital role in reflecting a nation’s culture and preserving its historical memory. They provide deep insights into societal values, traditions, perspectives, and lifestyles. The national cultural elements embedded in English and Uzbek folk songs carry distinct meanings, offering a lens through which to understand the cultural essence of each nation. This article explores the significance of these elements as expressed in English and Uzbek folk traditions.
Keywords: folklore; oral tradition; modern genres; lapars